E-learning in aviation - Kearns, Suzanne K. (Ashgate studies in human factors for flight operations., 2010)
Whereas traditional classroom instruction requires pilots to be pulled "off the line", a training facility to be maintained and instructors to be compensated, e-learning is extremely cost-effective and therefore an attractive alternative. However, e-learning only saves money if the training is effective. Eager to reap financial benefits, e-learning courses have a history of varying dramatically in quality. The poorest courses are those that directly convert classroom-based presentations to an online format, not recognizing that computer-based instruction is an entirely different medi